Brace-to-frame connection modelling effects on seismic loss assessment of steel concentrically-braced frames. (September 2020) - Silva, A.; Castro, J.M.; Monteiro, R.
Abstract: The main objective of this study is to investigate the implications of the explicit brace-to-frame gusset connection modelling on the seismic performance assessment of steel concentrically-braced frames (CBFs). Two key modelling alternatives are considered, namely through the simulation of CBFs with: i) a benchmark experimentally-validated model, in which the gusset plates are explicitly designed and simulated; and ii) a more simplified option, whereby diagonals are simulated through a centreline-to-centreline approach with fully-pinned boundary conditions. Anticipating the consequences of a less refined modelling approach, a simplified regression-based design process to Eurocode 8 for these gusset connections is proposed, therefore avoiding the need for an explicit connection design for seismic assessment purposes. A third modelling option, an identical approach to the benchmark but with the gusset dimensions being determined through the aforementioned regression-based design process, is also considered. The importance of the explicit modelling of the gusset plate connections to obtain reliable estimates of seismic performance is shown through the comparison of the seismic performance of various building archetypes, considering different metrics (e.g. lateral deformations, earthquake-induced collapse risk and economic losses). Furthermore, the validity of the proposed gusset-design methodology is discussed, by comparing the resulting gusset dimensions against those associated with a rigorous seismic design process, as well as by comparing the seismic performance assessed with numerical models incorporating explicitly-designed or simplified-designed gusset geometries. Highlights: The influence of brace simulation via simplified idealizations on the seismic performance assessment of CBFs is examined. The importance of explicit modelling of the brace-to-frame connection for seismic performance assessment is shown. A practical approach for the definition of the geometry of brace-to-frame gusset plate connections is proposed. The proposal results in identical estimates of seismic performance in comparison to the use of detailed connection design.